Phenolic compounds occurrence and human health risk assessment in potable and treated waters in Western Cape, South Africa - Mhlongo, Nkosiyenzile Londiwe; Akharame, Michael Ovbare; Pereao, Omoniyi; Human, Izanne Susan; Opeolu, Beatrice Olutoyin (Frontiers in Toxicology, 2024)
Phenolic pollutants from industrial and agricultural activities pose a major threat to the world's potable water supply. The persistent micro-pollutants often find their way into drinking water sources with possible adverse human health implications. In this study, bottled water, tap water, and wastewater treatment plant (WWTP) effluent samples from the Boland region of the Western Cape, South Africa were assessed to determine 4-chlorophenol (4-CP) and 2,4-dichlorophenol (2,4-DCP) levels using HPLC/DAD instrumentation. Evaluation of the human health risk (cancer risk) for the pollutants was conducted using the hazard quotient (HQ). The Ames mutagenicity test was also conducted using the Salmonella typhimurium T98 and T100 strains and the S9 activation enzyme. Trace levels of the phenolics were detected in the samples with a range of 9.32 x 10 -7 -1.15 x 10 -4 mg/L obtained for 4-CP, and 8.80 x 10 -7 -1.72 x 10 -4 mg/L recorded for 2,4-DCP. Both compounds had levels below the limit of 0.01 mg/L prescribed by South African legislation. The assessed HQ for the phenolic concentrations indicates a low level of potential ecological risk and none of the samples had a cancer risk value that exceeded the regulatory limit. The possibility of the analyzed samples causing cancer is unlikely, but non-carcinogenic adverse effects were found. Strong mutagenicity was observed for the T98 strains with a potential ability to cause mutation toward the insertion or deletion of a nucleotide. The T100 bacterial strain showed very slight mutagenicity potential, however, it is unlikely to cause any mutation.